2009
DOI: 10.5012/bkcs.2009.30.12.2883
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-Assisted Synthesis of 3-Styrylchromones in Alkaline Ionic Liquid

Abstract: A simple, highly efficient and environmentally benign method for the synthesis of 3-styrylchromones from 3-formylchromones and 4-nitrophenylacetic acid/4-nitrotolune in the presence of catalytic amount of basic ionic liquid 1-butyl-3-methylimidazolium hydroxide [(bmim)OH] carried out under the influence of microwave irradiation. This method gives remarkable advantages such as, short reaction times, simple work-up procedure and moderate to good yields. The ionic liquid was successfully reused for four cycles wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Comparisons of efficacy of CuB 4 O 7 with those of the reported catalysts 70–91 for the synthesis of 2,4,5-trisubstituted imidazole have shown that the present system involving CuB 4 O 7 has proven to be more efficient in terms of the short reaction time, milder reaction condition, and product yields (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…Comparisons of efficacy of CuB 4 O 7 with those of the reported catalysts 70–91 for the synthesis of 2,4,5-trisubstituted imidazole have shown that the present system involving CuB 4 O 7 has proven to be more efficient in terms of the short reaction time, milder reaction condition, and product yields (Table 4).…”
Section: Resultsmentioning
confidence: 87%
“…Consequently, the reaction conditions used in the synthesis of chromene derivatives from dimedone may not be suitable when tetronic acid is used as the 1,3-dicarbonyl compound. 20 21 22 23…”
Section: Table 1 Optimization Studies Under Conventiona...mentioning
confidence: 99%
“…The basic [bmim]OH IL catalyzed the synthesis of 3-styrylchromones from 3-formylchromones and a carbanion precursor, under MW irradiation [104] (Scheme 35). The authors pointed at the advantages of the method (easy work-up, short reaction times, satisfactory yields, reusable catalyst) and at the cytotoxicity of products.…”
Section: C-cbond Formation With C-nucleophilic Reagentsmentioning
confidence: 99%